Study on the reactive power coordinated control in hybrid parallel HVDC system. Issue 1 (May 2020) - Han, Yan; Rui, Song; Xuan, Wang; Shichang, Zhao; Wenli, Yang; Min, Luo
Abstract: Hybrid parallel HVDC system adopts line commutated converter high voltage direct current(LCC-HVDC) and voltage source converter high voltage direct current(MMC-HVDC) parallel structure, which combines the advantages of LCC-HVDC and MMC-HVDC. Based on the existing reactive power control of HVDC system, the reactive power coordination control strategy of hybrid parallel HVDC system is innovatively proposed in this paper. Firstly, the reactive power control of LCC-HVDC and MMC-HVDC are studied respectively. And then the voltage stability of LCC-HVDC fed weak AC system is analyzed. Furthermore, a reactive power coordination control strategy between reactive power compensation device of the converter station and MMC-HVDC is proposed. Finally, based on PSCAD/EMTDC simulation platform, a hybrid parallel HVDC simulation system is built. The reactive power coordination control strategy under steady and transient conditions is simulated and analyzed respectively. The analysis results show that the reactive power coordinated control strategy can suppress the voltage fluctuation of converter bus in steady state. At the same time, the reactive power coordinated control strategy can restrain the commutation failure of LCC-HVDC in the fault of receiving power grid and improve its fault recovery ability.